2017
DOI: 10.4172/2327-4972.1000215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Corticosteroid Therapy on Respiratory Morbidity in Infants Borne at Term by Elective Cesarean Section at Omdurman Maternity Hospital

Abstract: Objectives: A study done in Omdurman Maternity Hospital (OMH) during 2013, to study the effect of corticosteroid administration two days before an elective caesarean section to reduce the respiratory morbidity in infants born. Methodology:It is a randomized control trial study comparing prophylactic antenatal corticosteroids with no treatment given before elective caesarean section C/S.Results: A total of 560 patients of 5421 who underwent elective caesarean section C/S in 2013, were randomly selected, 281 (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…After the duplicates were removed, 176 records were screened for inclusion based on their titles and abstracts. The full texts of the remaining 19 articles were reviewed, and nine articles that fulfilled our predetermined criteria were included in our systematic review and meta-analysis [16][17][18][19][20][21][22][23][24]. The flow chart for study selection according to PRISMA guidelines is shown in Figure 1.…”
Section: Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the duplicates were removed, 176 records were screened for inclusion based on their titles and abstracts. The full texts of the remaining 19 articles were reviewed, and nine articles that fulfilled our predetermined criteria were included in our systematic review and meta-analysis [16][17][18][19][20][21][22][23][24]. The flow chart for study selection according to PRISMA guidelines is shown in Figure 1.…”
Section: Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Ontela -2018 [19], Attawattanakul -2015 [18], Nabhan -2014 [23], Elbohoty -2020 [21], Afzal -2019 [16], Sadiq -2019 [22], Ismail -2017 [24], Nooh -2017 [20], Ahmed -2015 [17].…”
Section: Figure 4: Bias Assessmentmentioning
confidence: 99%
“…It constitutes about 30-40% of births, of which around half are elective births. 1 Caesarean section is a major operation that increases both mother and baby's short-term and long-term adverse effects. 2 Caesarean section rate increase is a global phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…4 According to national sentinel caesarean section audits, in United Kingdom rate of abdominal births is 67% in women with previous caesarean as compared to 34% in primigravidas. 5 Infants born after caesarean delivery are more likely than in vaginally born infants to have respiratory morbidity, and this risk increases further, with potentially severe implications for the subset of children delivered after elective caesarean section 1 . Neonatal respiratory distress syndrome (RDS) is a condition of pulmonary insufficiency that begins at or shortly after delivery and increases in severity over two days of life 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal respiratory complications like respiratory distress syndrome (RDS) and transient tachypnea of newborn (TTN) are more common in infants delivered via LSCS as compared to those delivered vaginally. Studies have shown that about 50 % of neonates with RDS were due to the iatrogenic 5,6 early term caesarean section. Apart from mode of delivery, the gestational age at the time of delivery also affects 5 the neonatal respiratory outcomes.…”
mentioning
confidence: 99%